2018
DOI: 10.1002/pen.25039
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of composites based on polyoxymethylene and effect of silicone addition on mechanical and tribological behavior

Abstract: Additives to polymer materials allow to obtain a wide range of functional properties. The improvement of wear and durability of plastics is achieved by the use of powder or fibrous fillers and complex modifications of structure. The aim of the work was to examine the physical, mechanical and tribological properties of modified polyacetal. As a modifiers various types of silicon, thermoplastic polyurethane and aramid fiber were used. The addition of above mentioned additives reduces the coefficient of friction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 16 publications
1
18
0
1
Order By: Relevance
“…Nanocomposites are multi‐phase solid materials in which the fillers have at least one dimension ≤100 nm. Owing to the high surface area to volume ratio of the nano‐sized fillers combined with the quantum size effect, nanocomposite materials often exhibit improved properties compared with their bulk counterparts . Polyacrylamide (PAAM) is a synthetic linear, insulating and polar polymer having (CO‐NH 2 ) groups that have strong interfacial interactions with other polymers and enable the polymer to form hydrogen bonds with drug molecules, facilitating drug diffusion and release .…”
Section: Introductionmentioning
confidence: 99%
“…Nanocomposites are multi‐phase solid materials in which the fillers have at least one dimension ≤100 nm. Owing to the high surface area to volume ratio of the nano‐sized fillers combined with the quantum size effect, nanocomposite materials often exhibit improved properties compared with their bulk counterparts . Polyacrylamide (PAAM) is a synthetic linear, insulating and polar polymer having (CO‐NH 2 ) groups that have strong interfacial interactions with other polymers and enable the polymer to form hydrogen bonds with drug molecules, facilitating drug diffusion and release .…”
Section: Introductionmentioning
confidence: 99%
“…With increasing fiber content, the coefficient of friction and wear are reduced [6,[32][33][34]. Subsequent fillers use to improve the properties of polyoxymethylene composites are low density polyethylene (LDPE) and wood grain, copper particles or basalt fibers, all of these additives modify POM composites in the direction of develop its strength, thermal, and tribological properties [20,26,27,35,36].In this work, polyoxymethylene composites reinforced with glass fiber (cut roving, with diameter of 10 and 13 µm, and length about 150-200 µm) and carbon fibers (diameter of 7 µm and length about 3 mm) were analyzed. Research showed the effect of used reinforcements on strength properties and behavior of composites under dynamic load.…”
mentioning
confidence: 99%
“…Other particles were, for example, nano silica particles addition to enhance strength and thermal properties, or synthetic oil and Teflon particles for better tribological properties. [ 3–10 ] The positive effects of other metal particles such as aluminum, nickel, and silver particles have also been proven. Brostow et al indicated an increase in the strength properties of polyethylene after the introduction of metal particles, however, these properties depended on the quantity.…”
Section: Introductionmentioning
confidence: 99%